Mechanical properties of Cissus quadrangularis stem fibre reinforced isophthalic polyester composites. (14th May 2021) - Veeranna, M.; Arunkumar, D.T.; ,; Pattanaik, A.; Rao, P.S. Raghvendra; Sreenivasulu, G.
Current research work deals with the mechanical properties of Cissus quadrangularis stem natural fibre (CQSF) with polyester matrix. The fibre was extracted with water and subjected to different pretreatment to remove the wax content from the surface of the fibre and to improve adhesive bonding and strength of the fibre. Fabrication of the natural fibre reinforced composites (NFRCs) with polyester matrix was prepared, followed by mechanical performance of NFRCs composites. The result shows improved mechanical properties with increase in CQSF content up 25 wt%. Further morphological analysis was done on the fractured surfaces of composites with scanning electron microscopes.